Questioning Borders in Adaptation and Illustration: Where the Wild Things Are and the Adaptation of Synchronically Illustrated Literature to Film - Silva, Vitor Joel Alves (Cadernos de Literatura Comparada, 2023)
Using Where the Wild Things Are as a case study, this article aims to challenge prevailing paradigms within illustration and adaptation theory. Drawing on the concept of cooperation/competition, established definitions of illustration and the increasing trend of adapting picture books into films, I critically examine the limitations in the discourse within these fields, highlighting challenges in adequately addressing the objects they seek to explain. Through three key observations centered on synchronic illustration processes, subsequent adaptation networks, and Linda Hutcheon’s notion of the source text as a “haunting” mechanism, I identify inherent shortcomings in the referred paradigms, ultimately suggesting the need for additional qualitative and quantitative research.